Analysis on the performances of autoclaved aerated concretes - Muhamad Hisyamuddin, Jaffar (2013)
Nowadays, with the development of the economy in recent years, the people standard quality of living also increases as the Malaysia has been maintaining high economic growth and thus, contributed to the rapidly rising of the energy consumption. About 45% of the total electricity used in the residential building sector for cooling accounts of air conditioning. This study deals with the optimum thickness of Autoclaved Aerated Concrete (AAC) of building constructions and the thermal performances of buildings with different wall systems in a Tropical Region. The results show that the optimum thickness of AAC wall orientation was 66mm varies from standard common practice of 100mm with the total annual cooling loads of 84957Wh and 79138Wh with the annual electricity costs of RM2209 and RM2062 per year respectively. While, the standard sand cement brick with and without insulation wall orientation with thickness of 209 mm and 152 mm, the total annual cooling loads was 87819Wh and 97604Wh with annual electricity costs of RM2283 and RM2538 per year respectively.. This research uses Autodesk Revit for building modeling and Autodesk Ecotect Simulation software to analyze the building energy performances in terms of cooling loads. The investigation is carried out for the building with the climatic condition of Malaysia. The results are compared between the four different wall systems of AAC with optimum thickness, AAC with standard common practice thickness, standard sand cement brick with insulation and standard sand cement brick without insulation wall systems in terms of optimum thickness and thermal with the costs performances and payback period of the building.